Frequency and Time-frequency-based Analysis of Pressure Drop Signals in Structured Packed Columns - Pietro Giustacori; Leonardo Zando; Riccardo Bacci Di Capaci; Elisabetta Brunazzi (Chemical Engineering Transactions, 2025)
This study introduces a comprehensive novel analysis of pressure drop signals in both flooded and partially flooded packed beds. Pressure measurements were taken during column operation at various liquid loads and gas superficial velocities. Different liquid loads were investigated to enable a detailed study of the dynamic behavior of the structured packing during the onset of flooding. Two complementary methods were used for data analysis, a Fast Fourier Transform (FFT) was used to identify the dominant frequencies associated with the flooded stationary state. Then, a wavelet transform-based analysis enabled a novel high-resolution time-frequency representation, revealing the precise temporal evolution of flooding dynamics. This new method facilitates the characterization of the transition from incipient flooding to fully developed flooding, and its rapid propagation from the inter-packing zone. Understanding this dynamic behavior is crucial for online monitoring, prediction, and anticipation of flooding events, thereby enhancing operational control and efficiency of structured packed column systems.